Indebtedness: An entrepreneurial strategy to establish barriers to entry in Colombia in the 1995-2003 period? (2008)
This article is an extension of the work of Martin (2003) and it examines whether firms use debt strategically to stop entry of potential rivals in their industry. By using Generalized Method of Moments estimation (GMM), we evaluate the effects of assets, market share and size as proxies for market revenue, and the entry barriers due to indebtedness levels. Our data uses firmlevel information for Colombia from 1995-2003, and we introduce a dummy variable for taking into account the industrial effect. We find that firms use assets to limit entry and that indebtedness decreases as firms increase their market share.